A High-Throughput Screening Method for Determining the Optimized Synthesis Conditions of Quinoxaline Derivatives Using Microdroplet Reaction - Yang, Yanmei; Liu, Junmin; Chen, Zhenzhen; Niu, Weihua; Li, Ran; Niu, Le; Yang, Peng; Mu, Xiaoyan; Tang, Bo (Frontiers in Chemistry, 2020)
Quinoxaline derivatives demonstrate many distinguished chemical, biological, and physical properties and have a wide application in dyes, electroluminescent material, organic semiconductors, biological agents, etc. However, the synthesis of quinoxaline still suffers from several drawbacks, for instance, longer reaction time, unsatisfactory yields, and use of metal catalysts. Here, utilizing microdroplet-assisted reaction, we demonstrate the successive synthesis of several important quinoxaline derivatives. For case studies of 1H-indeno [1, 2-b] quinoxaline and 3,5-dimethyl-2-phenylquinoxaline, the present microdroplet approach can complete in milliseconds and the conversion rate reached 90% without adding any catalyst, which is considerably quicker and higher than conversional bulk-phase reactions. When combined with MS detection, high-throughput screening of the optimal reaction conditions can be achieved. Several impacts of droplet volume, reaction flow rate, distance from the MS inlet, spray voltage, and flow rate of the auxiliary gas can be screened on-site quickly for enhanced reaction speed and yields. More importantly, this platform is capable to be used for the scaled-up microdroplet synthesis of quinoxaline diversities. Considering the facile, economic, and environmentally friendly features of the microdroplet approach, we sincerely hope that the current strategy can effectively promote the academic research and industrial fabrications of functional quinoxaline substances for chemical, biological, and pharmaceutical application developments.